An Incentive And Trustworthy Systems With E-Star For Heterogenous Multihop Wireless Networks - Megha Rani, R; Harshavardhan, H (International Journal of Computer Sciences and Engineering, 2025)
For establishing stable and reliable routes in heterogeneous multi-hop wireless networks (HMWNs) a secure protocol for Establishing STable and reliable Routes (E-STAR) is proposed. It integrates incentive and trust systems with a trust-and energy-aware routing protocol. Compensating the nodes that relay others packets and charge those that send packets are main aims of incentive systems. The nodes competence and reliability in relaying packets in terms of multi-dimensional trust values are main attractions. The trust values are attached to the nodes public-key certificates to be used in making routing decisions. Two routing protocols is developed to direct traffic through those highly-trusted nodes having sufficient energy to minimize the probability of breaking the route. By this way, E-STAR can prompt the nodes in maintaining route stability and reporting correct battery energy capability. Because any loss of trust will result in loss of future gains. Moreover, for the efficient implementation processing the incentive receipts for computing trust values are necessary. Analytical results demonstrate protocol is without false allegations. Improvement in the packet delivery ratio and route stability are proved through simulation results.